The Evaluatıon Of Natural Head-Neck Posture And Cranıofacıal Morphology In Dıfferent Head Types - T. Ufuk Toygar Memikoğlu; Ayşegül Köklü (Galenos Yayinevi, 1997)
The aim of this study was to evaluate the craniofacial morphology in individuals with hiperbrachycephal, brachycephal, mesocephal and dolichocephal head types, regarding their natural head and neck postures. The sample comprised lateral cephalometric radiographs taken at the natural head position of 114 subjects in the range of 19-29 years of age. Craniofacial morphology and natural head and neck postures of four head types were assessed according to the intra- and extracranial reference planes using 37 measurements. Statistical evaluation was carried oui on four groups defined according to head types, using correlation analysis between cephalic index, maximum width and length measurements and postural parameters, besides ANOVA and Duncan test. The findings of this study showed that when head types were classified according to cephalic index, significant differences were found only in sagittal and vertical, cranial measurements. The head types were not considerably associated with head and neck posture and craniofacial morphology when evaluated using both intra- and extracranial reference planes. Still, it should not be neglected that there may be different anatomic characteristics of head and cervical column relationship according to head type.